Comparison of sexual function between laparoscopic lateral suspension and laparoscopic sacrocervicopexy with the use of the PISQ-IR questionnaire - Malanowska-Jarema, Ewelina; Starczewski, Andrzej; Melnyk, Mariia; Fidalgo, Daniel; Oliveira, Dulce; Dubuisson, Jean (Frontiers in Medicine, 2024)
Introduction and hypothesis: We aimed to analyze the quality of sexual life of patients with apical vaginal wall prolapse who had undergone laparoscopic lateral suspension ( LLS) and laparoscopic sacrocolpopexy (LSC). Methods: We performed a secondary analysis of sexual outcomes of a previous randomized control trial comparing LLS and LSC in 89 women with symptomatic POP stage ≥ II. We evaluated sexually active (SA) and non-sexually active women (NSA) using the Pelvic Organ Prolapse/Incontinence Sexual Questionnaire-IUGA-Revised (PISQ-IR). Women were reviewed over a period of 1 year post-surgery. Results: Analysis of the entire PISQ-IR questionnaire indicates that surgical treatment of POP resulted in an improvement of the quality of sexual life in 21 (80.76%) in the group of sexually active women after LSC and in 20 (83.33%) in the group of SA patients after LLS. In both groups of patients, dyspareunia was not observed. Conclusions: In conclusion, the quality of sexual life in SA group of patients improved significantly after both surgical procedures. The quality of sexual life of surveyed women significantly improved after curing POP symptoms.